University students’ subject matter knowledge and misconception of teaching games for understanding and its implication to teaching practice - Jani, Julismah; Pearson, Phil; Webb, Paul (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This study is to track the subject matter knowledge of and misconception about Teaching Games for Understanding (TGfU) of fourth year undergraduate pre-service teachers‟ physical education majors at an Australian university. The test of reliability on misconception scale are subjected to a Rasch analysis (KR-20 = .52) which consists of 20 dichotomous questions with true/false answers. Analyses of the data reveal that students achieve a credit on subject matter knowledge and attain four misconceptions about TGfU. There is a significant (p < 0.05) difference in the scores for subject matter knowledge and concepts of TGfU through paired samples t test. These results imply that subject matter knowledge does have an effect on students‟ concepts of TGfU but with very low relationship (r(53 = .19, p < 0.05). The implication of content knowledge to teaching is to resist the pre-concept or misconception of the subject matter. If pre-service teachers are to improve the quality of teaching and learning in content areas, he or she needs to possess a deep understanding of games both within and across categories in TGfU. Misconceptions tend to be very resistant to instruction because learning entails replacing or radically reorganizing student knowledge. This puts teachers in the very challenging position of needing to bring about significant conceptual change in student knowledge. Therefore pre-service teachers must know the subject matter they teach and their performance will be determined by the depth of their content knowledge in relation to teaching, making this an essential component to their teaching practice. Teachers must know the subject they teach and this is important to teacher competency.